Testing the Assumptions of Slippery Slope Framework on Tax Compliance: Evidence from Nigerian SMEs - Ayuba, Augustine; Saad, Natrah; Zainal Affrin, Zaimah (De La Salle University, 2018)
This paper integrates the assumptions of the Slippery Slope Framework in explaining the tax compliance of small and medium enterprises. This study tests these assumptions in relation to SMEs taxpayers to further reestablish the applicability of the framework with different kinds of taxpayers. Partial Least Squares Structural Equation Modeling (PLS - SEM) further supported the framework in analyzing the data of this study. The findings reveal that perceived corruption along with perceived service orientation strongly interact each other in expounding the paradox surrounding tax compliance.